Cross-Cultural Social Integration of Japanese Elderly Long Term Stay in Chiang Mai - Promtong, Thitima (Rajapark Journal, 2022)
The purpose of this qualitative research was to examine the integration of cross-cultural society of the Japanese elderly staying long-term in Chiang Mai. The key informants selected by purposive sampling included 12 Japanese, 60 years of age or older, holding a Non-Immigration Visa, code O-A (Long-Stay), staying in Chiang Mai for more than seven years, and being able to provide clear information on the studied issues. Data were collected by conducting in-depth interviews and observing forms. Content and theme analysis were employed to analyze the obtained data for summarizing the research results. The qualitative findings revealed that the most effective social integration among the Japanese elderly was functional integration, which involved the interdependence between different functions existing in society at the level of individuals, coteries, and organizations. The Japanese elderly had been given a new role that could build relationships with people in the community, integrating new roles in participating in the community in a variety of activities, which made it possible to integrate happily with long-term residency in Chiang Mai despite social and cultural differences. As for communicative integration, it was found that the Japanese elderly were likely to have less integration than other aspects.